Evaluation of Four Malaria Rapid Diagnostic Test Kits Used at the Enyiresi Government Hospital in the Eastern Region of Ghana - Seth A. Domfeh; Boateng Y. Darkwa; Raymond K. Gablah; Evans Adu-Asamoah; Christian Obirikorang (Journal of Parasitology Research)
Microscopic identification of Plasmodium spp. is the gold standard for malaria diagnosis. However, malaria rapid diagnostic test kits are also available for prompt diagnosis. This study evaluated four routinely used malaria rapid diagnostic test kits at the Enyiresi Government Hospital in the Eastern Region of Ghana. This cross-sectional study was conducted among 238 patients suspected of malaria. Venous blood samples were collected to identify Plasmodium falciparum using microscopic techniques. Further, the performances of four malaria rapid diagnostic test kits, First Response Malaria Ag Pf, Carestart Malaria Pf, SD Bioline Ag Pf, and ABON Malaria Pf, were evaluated using the results from the microscopy as the standard reference. As confirmed by microscopy, 65.5% (156/238) of the patients have falciparum malaria. All malaria rapid diagnostic test kits had sensitivities and specificities over 75% compared to microscopy results as the reference standard. However, the SD Bioline Ag Pf kit recorded the highest agreement with the microscopy (Cohen’s kappa=0.879). All the malaria rapid diagnostic test kits performed quite well and can be used in emergencies. However, results from these kits need to be confirmed by microscopy.